Quality of the Diagnostic Process, Treatment Decision, and Predictors for Antibiotic Use in General Practice for Nursing Home Residents with Suspected Urinary Tract Infection - Stine Dyhl Sommer-Larsen; Sif Helene Arnold; Anne Holm; Julie Aamand Olesen; Gloria Cordoba (MDPI AG, 2021)
Urinary tract infections (UTIs) are common in nursing home (NH) residents and Denmark is one of the countries with the highest antibiotic use in NHs. The aim of this study was to assess the quality of the diagnostic process and treatment decision on the day of the first contact from NHs to general practice and assess predictors for prescription of antibiotics in NH residents without an indwelling urinary catheter. The study was a prospective observational study in general practice in the Capital Region of Denmark; 490 patients were included; 158 out of 394 (40.1%, 95% CI 35; 45) patients with suspected UTI had urinary tract symptoms; 270 out of 296 (91.2%, 95% CI 87; 94) patients without urinary tract symptoms had a urine culture performed. Performing urine culture in the general practice was inversely associated to prescription of antibiotics on day one (OR 0.27, 95% CI 0.13; 0.56). It is imperative to support the implementation of interventions aimed at improving the quality of the diagnostic process on day one, as less than half of the patients given the diagnosis "suspected UTI" had urinary tract symptoms, and most patients without urinary tract symptoms had a urine culture performed.